Agreement between physiotherapists rating scapular posture in multiple planes in patients with neck pain: Reliability study. Issue 4 (December 2015) - O'Leary, Shaun; Christensen, Steffan W.; Verouhis, Alexis; Pape, Morten; Nilsen, Oivind; McPhail, Steven M.
Abstract: Objective: Evaluation of scapular posture is an integral component of the clinical assessment of painful neck disorders. The aim of this study was to evaluate agreement between therapist judgements of scapula posture in multiple biomechanical planes in individuals with neck pain. Design: Inter-therapist reliability study. Setting: Research laboratory. Participants: Fifteen participants with chronic neck pain. Main outcome measures: Four physiotherapists recorded ratings of scapular orientation (relative to the thorax) in five different scapula postural planes (plane of scapula, sagittal plane, transverse plane, horizontal plane, and vertical plane) under four test conditions (at rest, and during three isometric shoulder conditions) in all participants. Inter-therapist reliability was expressed using both generalized and paired kappa coefficient. Results: Following adjustment for expected agreement and the high prevalence of neutral ratings (81%), on average both the generalised kappa (0.37) as well as Cohen's Kappa for the two therapist pairs (0.45 and 0.42) demonstrated only slight to moderate inter-therapist reliability. Conclusions: The findings suggest that ratings of scapular posture in individuals with neck pain by visual inspection has only slight to moderate reliability and should only be used in conjunction with other clinical tests when judging scapula function in these patients.